TUBEROZ SKLEROZ KOMPLEKSİ - BENLİ, Sibel and CAN, Ufuk and SEÇKİN, Deniz and CANER, Hakan and ALTINÖRS, Nur and COŞKUN, Mehmet (Cerrahpaşa Medical Journal, 2014)
Background and Observation. Tuberous sclerosis complex is a hamartamatosis which mainly effects central nervous system, skin, kidney, liver and heart. The predominant neurologic manifestations are seizure and mental retardation. A 39yearold female patient with late onset seizure and typical skin findings and her sons are presented and this clinical entity 13 reviewed with are emphasis on the importance of systemic family screening.